Propuesta de mejoramiento de la productividad en el proceso Mixer mediante la utilización de la filosofía Lean manufacturing, y sus herramientas TPM y 5’s (2020)
The industrial environment is increasingly demanding, companies face changes constants to which they have to adapt to stay within the market. In addition, with the globalization of markets and the advancement of information and communication technologies (ICTs). For this reason, a great interest among managers in raising their quality standards, being more competitive and thus remain in the market. It has been shown that companies that do not permanently adapt to the requirements and needs of their environment do not achieve success, they even reach perish with time. By determining your shortcomings and working based on solve them before the effects are inevitable, as well as establish the opportunities and take advantage of it to your advantage, this should be an constant in industries. Therefore, continuous improvement and excellence operational in the processes is not should be optional, it is imperative, since when the term improvement is spoken it is quickly linked to management quality.